HUMAN CAPITAL STRATEGY AND DEVELOPMENT OF MSME PERFORMANCE: CASE STUDY OF SUKABUMI ANGET BREAD BUSINESS PERFORMANCE - Mintawati, Hesri (Penerbit Lafadz Jaya, 2025)
This study analyzes the human resource development of Roti Anget Sukabumi and aims to improve the performance of MSMEs by managing human resources to achieve performance. Small and medium enterprises (MSMEs) are the most important joint ventures in Indonesia's economic activities. The food industry in particular recorded very positive developments and contributed significantly to the country's economic growth. Bread is one of the alternative substitutes for instant food and is very popular among the general public because it is convenient and can be enjoyed by all circles. The research method used is qualitative. Data obtained in the study using observation, interviews, and documentation tools. Research findings show that companies provide human resource management to capitalize on potential market opportunities in the bakery industry. The increasing number of bread producers and consumers will affect the increasing competition among bakery companies. The purpose of this study is to determine the strategy of human resource management (MSMEs) to strengthen the national economy in the Anget Bread business. The conclusion that can be drawn from this study is that, given the importance of human resources in company activities, companies not only need to rely on technological advantages and financial resources, but also manage their human resources optimally. Also about the human factor. Of course, to achieve business results requires the provision of competitive and high-quality human resources.